FeCuCoOx nano solid solution, preparation method thereof and application of FeCuCoOx nano solid solution in degradation of organic pollutants

Through the FECUCOOX nano -solid -solid -solid -solid -solid -solid -solid -solid -solid -solid -solid -solid -soluble co -mixed technology, it solves the defects of nanozyme in terms of stability and recycling, realizes the degradation of efficient catalytic and environmentally friendly organic pollutants, reducing costs and avoiding secondary pollution.

CN119327456APending Publication Date: 2025-01-21SHAANXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411620273.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing nanoenzymes have defects in stability, biocompatibility, recycling and recycling, resulting in poor catalytic activity and secondary pollution risks, and high preparation costs and difficulty in large-scale production.

Method used

The oxide nanocrystal formed by the co-doping of three metal ions, Fe, Cu, and Co, namely FeCuCoOx nanosolid solution, enhances the catalytic activity and stability of the nanozyme, and uses its magnetic properties to achieve separation, recovery and recycling.

Benefits of technology

It improves the catalytic activity and stability of nanozymes, realizes efficient recovery and multiple recycling of nanozymes, reduces treatment costs and avoids the risk of secondary pollution, and has a good degradation effect on organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327456A_ABST
    Figure CN119327456A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano material synthesis and food safety, and relates to a FeCuCoOx nano solid solution and a preparation method and application thereof in organic pollutant degradation, the preparation method comprises the following steps: S1, mixing a FeCl2 solution, a CuCl2 solution and a CoCl2 solution, then dissolving in absolute ethyl alcohol, and carrying out ultrasonic uniform mixing, drying and grinding to obtain transition metal salt fine powder; s2, after NaNO3 is heated and melted, transition metal salt fine powder is added, and then oxide nanocrystals are formed through a reaction; and S3, cooling, cleaning and drying the oxide nanocrystal to obtain the FeCuCoOx nano solid solution. The FeCuCoOx nano solid solution prepared by the method disclosed by the invention can enhance the catalytic activity and stability of the nano enzyme, has magnetism, is convenient for realizing separation, recovery and cyclic utilization of the nano enzyme, and effectively avoids the risk of secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material synthesis and food safety and relates to a FeCuCoO x Nano solid solution, its preparation method and application in degradation of organic pollutants. Background Art

[0002] In the field of food safety, the degradation of organic pollutants is a crucial link. Traditional technologies use heat treatment and chemical disinfection to degrade organic pollutants in food. Although there are certain effects, the heat treatment and chemical disinfection methods have defects such as low efficiency, high energy consumption and the production of harmful by-products.

[0003] With the development of nanotechnology, nanozymes have become a new way to solve these problems due to their high catalytic activity and unique physicochemical properties. They show higher stability and lower inhibition sensitivity than traditional enzymes in a wider pH and temperature range, especially in the simulated Fenton reaction, by producing highly reactive hydroxyl radicals to degrade organic pollutants, showing great application potential. However, existing nanozymes still face challenges in stability, biocompatibility, and recovery and recycling in practical applications; not only do they lead to poor catalytic activity of nanozymes, but also because they cannot be recycled and recycled, there is a risk of secondary pollution; these not only increase the cost of degradation treatment, but also pollute the environment. In addition, the preparation cost and large-scale production of nanozymes are also key factors restricting their widespread application. Summary of the invention

[0004] Aiming at the technical defects of existing nanozymes in terms of stability, biocompatibility, recovery and recycling, the present invention provides a FeCuCoO x Nano solid solution, its preparation method and application in degradation of organic pollutants.

[0005] The present invention forms oxide nanocrystals by co-doping three metal ions of Fe, Cu and Co, namely FeCuCoO x Nano solid solutions can enhance the catalytic activity and stability of nanozymes, and have magnetic properties, which facilitates the separation, recovery and recycling of nanozymes, effectively avoiding the risk of secondary pollution.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A FeCuCoO x The preparation method of the nano solid solution comprises the following steps:

[0008] S1. Mixing FeCl2 solution, CuCl2 solution and CoCl2 solution to form a mixed solution, dissolving in anhydrous ethanol, and obtaining transition metal salt fine powder by ultrasonic mixing, drying and grinding; the molar ratio of FeCl2, CuCl2 and CoCl2 in the mixed solution is (1-3): (1-3): (1-2);

[0009] S2, heating and melting NaNO3, adding the transition metal salt fine powder in step S1, and then reacting to form oxide nanocrystals;

[0010] S3, the oxide nanocrystals in step S2 are cooled, cleaned and dried to obtain FeCuCoO x Nano solid solution.

[0011] It is further defined that in step S1, the ultrasonic mixing time is 30 min to 50 min, the drying temperature is 60° C. to 90° C., and the drying time is 6 h to 12 h.

[0012] It is further defined that in step S1, the average particle size of the transition metal salt fine powder is 5 microns.

[0013] It is further defined that in step S2, during the heating and melting process of NaNO3, the heating rate is 1°C / min to 5°C / min, the temperature is 300°C to 350°C, and the reaction time is 1h to 3h.

[0014] It is further defined that in step S3, the drying temperature is 40° C. to 65° C. and the drying time is 6 h to 12 h.

[0015] Using the FeCuCoO x FeCuCoO prepared by the preparation method of nano solid solution x Nano solid solution.

[0016] It is further defined that the FeCuCoO x The nano-solid solution is in the form of two-dimensional flakes and has magnetic recovery properties.

[0017] As described in FeCuCoO x Application of nano solid solutions in degradation of organic pollutants.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The FeCuCoO synthesized by the multi-metal ion co-doping strategy of the present invention x Nano solid solution, oxide nanocrystals formed by co-doping three metal ions of Fe, Cu and Co, namely FeCuCoO x Nano solid solution, through Cu2O and FeO xThe heterojunction between the nanozymes accelerates the reduction of surface Fe(III) generated in the Fenton reaction, which not only enhances the stability of the nanozyme but also exhibits efficient peroxidase-like activity, thereby improving the catalytic activity.

[0020] 2. FeCuCoO of the present invention x Nano solid solutions are magnetic, which facilitates the separation, recovery and recycling of nanoenzymes. They exhibit good recyclability and can be recycled multiple times, which not only reduces processing costs but also avoids the risk of secondary pollution.

[0021] 3. The present invention found through experiments that FeCuCoO x The nano solid solution showed good catalytic degradation effect on the common pollutant Rhodamine B (RhB), and had a preliminary degradation effect on microplastics. This shows that FeCuCoOx nano solid solution has a good degradation effect on organic pollutants.

[0022] 4. FeCuCoO provided by the present invention x The preparation method of nano solid solution is simple and low-cost, easy to achieve large-scale production, and easy to scale production. It provides a new efficient and environmentally friendly solution for the degradation of organic pollutants in food, and has important practical application value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 a is FeCuCoO x a is a scanning electron microscope image; b is a transmission electron microscope image; c is a total X-ray photoelectron spectrum; d is an X-ray diffraction spectrum;

[0024] Figure 2 a is FeCuCoO x Absorbance curve of TMB (3,3',5,5'-tetramethylbenzidine) under the action of peroxidase-like activity; b is FeCuCoO x Absorbance curve of ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt) under the action of peroxidase-like activity; c is FeCuCoO x Absorbance curve of OPD (o-phenylene phosphate disodium) under the action of peroxidase-like activity;

[0025] Figure 3 FeCuCoO x The degradation effect results; a is FeCuCoO x Color change of degraded Rhodamine B (RhB); b. FeCuCoO x Absorbance curve of RhB degradation; c. Absorbance curve of RhB degradation by different materials;

[0026] Figure 4 FeCuCoO x The color change during the degradation of Rhodamine B (RhB);

[0027] Figure 5 Trend graphs of degradation of organic pollutants for different materials;

[0028] Figure 6 FeCuCoO x Graph showing magnet recovery effects of nano solid solution. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0030] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0031] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.

[0032] It should also be understood that the specific embodiments described above are only used to explain the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the protection scope of the present invention / invention.

[0033] The present invention provides a FeCuCoO x The preparation method of the nano solid solution comprises the following steps:

[0034] S1. Mix FeCl2 solution, CuCl2 solution and CoCl2 solution to form a mixed solution, then dissolve in anhydrous ethanol, and obtain transition metal salt fine powder by ultrasonic mixing, drying and grinding.

[0035] In the present invention, the molar ratio of FeCl2, CuCl2 and CoCl2 in the mixed solution is (1-3): (1-3): (1-2); the volume ratio of the mixed solution to anhydrous ethanol is (9-12): (70-100).

[0036] Preferably, the molar ratio of FeCl2, CuCl2 and CoCl2 in the mixed solution is 1:1:1, 1:2:1, 1:2:2, 1:3:1, 2:1:1, 2:2:1, 2:3:1, 2:1:1, 2:2:1, 1:3:1, 1:3:2, 3:1:1, 3:1:2, 3:2:1, 3:2:2, 3:3:1, 3:3:2.

[0037] Preferably, the volume ratio of the mixed solution to anhydrous ethanol is 9:70, 9:80, 9:90, 9:100, 10:70, 10:80, 10:90, 10:100, 11:70, 11:80, 11:90, 11:100, 12:70, 12:80, 12:90, 12:100.

[0038] In step S1 of the present invention, the ultrasonic mixing time is 30 min to 50 min, the drying temperature is 60° C. to 90° C., and the drying time is 6 h to 12 h.

[0039] Preferably, the ultrasonic time is 30 min, 35 min, 40 min, 45 min or 50 min, the drying temperature is 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C; the drying time is 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0040] In step S1 of the present invention, the average particle size of the transition metal salt fine powder is 5 microns.

[0041] S2. After heating and melting NaNO3, add the transition metal salt fine powder in step S1, and then react to form oxide nanocrystals.

[0042] In step S2, during the heating and melting process of NaNO3, the heating rate is 1°C / min to 5°C / min, the temperature is 300°C to 350°C, and the reaction time is 1h to 3h.

[0043] Preferably, the heating rate is 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, the temperature is 300°C, 310°C, 320°C, 325°C, 330°C, 340°C or 350°C; and the reaction time is 1h, 1.5h, 2.0h, 2.5h or 3h.

[0044] S3, the oxide nanocrystals in step S2 are cooled, cleaned and dried to obtain FeCuCoO x Nano solid solution.

[0045] In step S3 of the present invention, the drying temperature is 40° C. to 65° C., and the drying time is 6 h to 12 h.

[0046] Preferably, the drying temperature is 40°C, 45°C, 50°C, 55°C, 60°C or 65°C, and the drying time is 6h, 7h, 8h, 9h, 10h, 11h or 12h.

[0047] FeCuCoO prepared by the above preparation method of the present invention xNano-solid solutions, which are in the form of two-dimensional flakes, have magnetic recovery properties, strong catalytic activity and stability, and can be used for the degradation of organic pollutants in food.

[0048] The preparation method and application of the present invention are described in detail below with several groups of embodiments.

[0049] It should be noted that, unless otherwise specified, the chemicals, reagents, etc. used in the following examples are all conventional commercial products in the art.

[0050] It should be noted that, unless otherwise specified, the operating steps used in the following embodiments are routine operations in the art.

[0051] Example 1

[0052] The FeCuCoO provided in this embodiment x The preparation method of the nano solid solution comprises the following steps:

[0053] S1. Take 20 mL of each of FeCl2 solution, CuCl2 solution and CoCl2 solution with a concentration of 1 mol / L, so that FeCl2, CuCl2 and CoCl2 are mixed in a molar ratio of 1:1:1, and then dissolve the mixed solution in 500 mL of anhydrous ethanol, and treat it by ultrasound for 30 minutes to achieve atomic-level uniform mixing.

[0054] S2. Place the solution after ultrasonic treatment in an oven and dry it at 75° C. for 12 h. Grind the dried solid into a fine powder of transition metal salt with an average particle size of 5 μm.

[0055] S3. Using a crucible as a reaction container, heat NaNO3 to 350°C in a muffle furnace at a heating rate of 5°C / min to melt it, then quickly add transition metal salt fine powder into the molten NaNO3, and maintain the reaction time for 2 hours to form oxide nanocrystals.

[0056] S4. After the reaction is completed, the obtained product (oxide nanocrystals) is quickly transferred to cold water for cooling, and then centrifuged and washed with a mixture of 70% (v / v) ethanol and 30% (v / v) water, and finally dried at 50°C for 6h to obtain FeCuCoO x Nano solid solution.

[0057] Example 2

[0058] The FeCuCoO provided in this embodiment x The preparation method of the nano solid solution comprises the following steps:

[0059] S1. Take 10 mL of 1 mol / L FeCl2 solution, 20 mL of 1 mol / L CuCl2 solution and 20 mL of 1 mol / L CoCl2 solution, and mix FeCl2, CuCl2 and CoCl2 in a molar ratio of 1:2:2. Then dissolve the mixed solution in 300 mL of anhydrous ethanol and treat it by ultrasound for 45 minutes.

[0060] S2. Place the solution after ultrasonic treatment in an oven and dry it at 60° C. for 10 h. Grind the dried solid into fine powder of transition metal salt with an average particle size of 5 μm.

[0061] S3. Using a crucible as a reaction container, heat NaNO3 to 330°C in a muffle furnace at a heating rate of 4°C / min to melt it, then quickly add fine powder of transition metal salt to the molten NaNO3, and maintain the reaction time for 2.5 hours to form oxide nanocrystals.

[0062] S4. After the reaction is completed, the obtained product (oxide nanocrystals) is quickly transferred to cold water for cooling, and then centrifuged and washed with a mixture of 90% (v / v) ethanol and 10% (v / v) water, and finally dried at 45°C for 8h to obtain FeCuCoO x Nano solid solution.

[0063] Example 3

[0064] The FeCuCoO provided in this embodiment x The preparation method of the nano solid solution comprises the following steps:

[0065] S1. Take 25 mL of 1.5 mol / L FeCl2 solution, 15 mL of 0.75 mol / L CuCl2 solution and 20 mL of 1.2 mol / L CoCl2 solution, and mix FeCl2, CuCl2 and CoCl2 in a molar ratio of 3:1:2. Then dissolve the mixed solution in 400 mL of anhydrous ethanol and treat with ultrasound for 60 min.

[0066] S2. Place the solution after ultrasonic treatment in an oven and dry it at 90° C. for 8 h. Grind the dried solid into a fine powder of transition metal salt with an average particle size of 5 μm.

[0067] S3. Using a crucible as a reaction container, heat NaNO3 to 320°C in a muffle furnace at a heating rate of 3°C / min to melt it, then quickly add fine powder of transition metal salt to the molten NaNO3, and maintain the reaction time for 1 hour to form oxide nanocrystals.

[0068] S4. After the reaction is completed, the obtained product (oxide nanocrystals) is quickly transferred to cold water for cooling, and then centrifuged and washed with a mixture of 60% (v / v) ethanol and 40% (v / v) water, and finally dried at 65°C for 10 h to obtain FeCuCoO x Nano solid solution.

[0069] Example 4

[0070] The FeCuCoO provided in this embodiment x The preparation method of the nano solid solution comprises the following steps:

[0071] S1. Take 15 mL of 1 mol / L FeCl2 solution, CuCl2 solution, and CoCl2 solution, respectively, and mix FeCl2, CuCl2, and CoCl2 in a molar ratio of 1:1:1. Then dissolve the mixed solution in 350 mL of anhydrous ethanol and treat with ultrasound for 30 min.

[0072] S2. Place the solution after ultrasonic treatment in an oven and dry it at 80° C. for 12 h. Grind the dried solid into a fine powder of transition metal salt with an average particle size of 5 μm.

[0073] S3. Using a crucible as a reaction container, heat NaNO3 to 300°C in a muffle furnace at a heating rate of 2°C / min to melt it, then quickly add transition metal salt fine powder into the molten NaNO3, and maintain the reaction time for 3 hours to form oxide nanocrystals.

[0074] S4. After the reaction is completed, the obtained product (oxide nanocrystals) is quickly transferred to cold water for cooling, and then centrifuged and washed with a mixture of 80% (v / v) ethanol and 20% (v / v) water, and finally dried at 55°C for 7h to obtain FeCuCoO x Nano solid solution.

[0075] Example 5

[0076] The FeCuCoO provided in this embodiment x The preparation method of the nano solid solution comprises the following steps:

[0077] S1. Take 12 mL of 0.8 mol / L FeCl2 solution, 25 mL of 1.2 mol / L CuCl2 solution and 18 mL of 1 mol / L CoCl2 solution, and mix FeCl2, CuCl2 and CoCl2 in a molar ratio of 1:3:2. Then dissolve the mixed solution in 450 mL of anhydrous ethanol and treat with ultrasound for 50 min.

[0078] S2. Place the solution after ultrasonic treatment in an oven and dry it at 50° C. for 12 h. Grind the dried solid into a transition metal salt fine powder with an average particle size of 5 μm.

[0079] S3. Using a crucible as a reaction container, heat NaNO3 to 340°C in a muffle furnace at a heating rate of 1°C / min to melt it, then quickly add transition metal salt fine powder into the molten NaNO3, maintain the reaction time for 2 hours, and form oxide nanocrystals.

[0080] S4. After the reaction is completed, the obtained product (oxide nanocrystals) is quickly transferred to cold water for cooling, and then centrifuged and washed with a mixture of 50% (v / v) anhydrous ethanol and 50% (v / v) water, and finally dried at 40°C for 12h to obtain FeCuCoO x Nano solid solution.

[0081] Furthermore, the FeCuCoO prepared above was tested by the following test: x The properties of nano solid solution are explained.

[0082] Test 1

[0083] FeCuCoO prepared in Example 4 x Nano-solid solution was taken as an example for characterization.

[0084] See also Figure 1 , Figure 1 a is FeCuCoO x SEM image of the nanosolid solution, showing the synthesized FeCuCoO x The nanosolid solution presents a flake-like structure, some of which have curled edges, forming a unique needle-like morphology. Figure 1 The TEM image in b shows that the material is a two-dimensional thin layer material, in which lattice fringes can be clearly observed on the curled flakes, indicating that the material has a high degree of crystallinity. Figure 1 c is FeCuCoO obtained by X-ray photoelectron spectroscopy x The elemental composition of the nano solid solution shows that Fe, Co, and Cu are evenly distributed in the nano solid solution in appropriate proportions, which helps to improve the catalytic performance of the material; Figure 1 d is the X-ray diffraction pattern, which further confirms the lattice type of the material. The main diffraction peaks match the standard card of CoFe2O4 (JCPDS No.22-1086), indicating that FeCuCoO x The nano-solid solution mainly inherits the spinel structure of CoFe2O4.

[0085] Test 2

[0086] FeCl2 solution was used to prepare Fe3O4 nanosheets (Fe3O4NPs) in the same manner as in Example 4 as a control sample. x Nano-solid solution was used as the test group sample.

[0087] The experimental process is: Fe3O4 nanosheets and FeCuCoO x The nano solid solution was mixed with ultrapure water at a ratio of 1:20 to obtain Fe3O4NPs solution and FeCuCoO x Solution, both solutions were mixed with 50 μL 500 mmol / L H2O2 and rhodamine B and incubated to clarify the pollutant degradation performance of the nanozyme.

[0088] 1. Enzyme catalytic activity test

[0089] The FeCuCoO in Example 4 was oxidized by catalytic oxidation of TMB (3,3',5,5'-tetramethylaniline), ABTS (2,2'-hydrazinobis(3-ethylbenzothiazoline-6-sulfonic acid) and OPD (o-phenylenediamine). x The peroxidase-like activity of the nano solid solution was evaluated. Fe3O4 nanosheets were used as a control. Under the action of different materials and H2O2, the darker the color of TMB, ABTS and OPD, the higher the peroxidase-like activity of the material.

[0090] See also Figure 2 The color development results of different color development substrates, FeCuCoO x The absorption peaks of the FeCuCoO x It has the highest peroxidase-like activity.

[0091] 2. Pollutant degradation

[0092] Taking the degradation of rhodamine B (RhB) as an example, the FeCuCoO x The degradation efficiency of nano solid solutions on pollutants was studied, and the degradation effect of Fe3O4 nanosheets (Fe3O4NPs) was used for comparison.

[0093] Experimental process: Fe3O4NPs and FeCuCoO x They were mixed with H2O2 in acetic acid-sodium acetate (NaAc-HAc) buffer solution (pH = 4.0) to form two reaction systems. 2 mL of RhB solution was then added to each reaction system with an initial concentration of 500 mg / L. The reaction was carried out at room temperature for 24 hours, and the degradation effect of RhB was detected by UV-visible spectroscopy. The degradation effects of different materials on RhB are shown in Figure 2. Figure 3 , Figure 4 and Figure 5 shown.

[0094] See also Figure 3 , Figure 3 a, FeCuCoO x The treated RhB achieved almost complete decolorization within 20 h, while the Fe3O4NPs-treated RhB did not completely decolorize within 20 h; Figure 3 b It can be seen that as time increases, the absorbance decreases significantly, indicating that the degradation effect increases with time; Figure 3 c It can be seen that after 20h of treatment with different materials, FeCuCoO x The absorbance of the group at the maximum absorption peak decreased most significantly. This indicates that FeCuCoO x Solid solution has a good degradation effect on organic matter.

[0095] See also Figure 4 ,FeCuCoO x The treated RhB solution achieved significant decolorization effect within 20 h.

[0096] See also Figure 5 The absorbance measurement results also confirmed that FeCuCoO x Effective degradation of organic pollutants. After 20 h of treatment with different materials, FeCuCoO x The fastest degradation rate.

[0097] Test 3

[0098] The FeCuCoO in Example 4 was studied by magnet adsorption experiment x Recyclability of solid solutions.

[0099] See also Figure 6 , confirming that FeCuCoO x The solid solution has magnetic properties, which facilitates the recycling of materials. In applications, FeCuCoO x Solid solution separation and recovery can achieve recycling, reduce costs and avoid secondary pollution.

[0100] The above test was conducted using FeCuCoO in Example 4. x The solid solution is completed, when the FeCuCoO in Examples 2 to 5 is x The solid solution is a sample, and it is found through verification that these samples have the same x The solid solution has the same or similar properties, and also has peroxidase-like activity, which has a good degradation effect on Rhodamine B organic matter.

[0101] The present invention adopts the technical strategy of multi-metal ion co-doping, and achieves the uniform distribution and synergistic effect of the three metal ions of Fe, Cu and Co in the nanostructure by precisely controlling the synthesis conditions, which not only enhances the catalytic activity of the nanozyme, but also significantly improves its stability in the complex food system. x Nano-solid solutions have shown extremely high efficiency in organic matter degradation, solving the problem of low efficiency in traditional Fenton reaction; FeCuCoO x The nano solid solution has efficient peroxidase-like activity, which can quickly catalyze the decomposition of H2O2 to produce hydroxyl radicals, thereby effectively degrading organic pollutants and inactivating microorganisms in food. At the same time, due to its magnetic properties, the nano solid solution can be separated from the food system by simple magnetic separation technology after completing the catalytic reaction, avoiding secondary contamination of food.

[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the present invention, although the present invention has been described in detail with reference to the preferred embodiments. It should be understood by those skilled in the art that the technical solutions of the present invention can still be modified or replaced by equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. FeCuCoO x The method for preparing a nano solid solution is characterized in that: The following steps are involved: S1. Mixing FeCl2 solution, CuCl2 solution and CoCl2 solution to form a mixed solution, dissolving in anhydrous ethanol, and obtaining transition metal salt fine powder by ultrasonic mixing, drying and grinding; the molar ratio of FeCl2, CuCl2 and CoCl2 in the mixed solution is (1-3): (1-3): (1-2); S2, heating and melting NaNO3, adding the transition metal salt fine powder in step S1, and then reacting to form oxide nanocrystals; S3, the oxide nanocrystals in step S2 are cooled, cleaned and dried to obtain FeCuCoO x Nano solid solution.

2. FeCuCoO according to claim 1 x The method for preparing a nano solid solution is characterized in that: In the step S1, the ultrasonic mixing time is 30 min to 50 min, the drying temperature is 60° C. to 90° C., and the drying time is 6 h to 12 h.

3. FeCuCoO according to claim 1 x The method for preparing a nano solid solution is characterized in that: In the step S1, the average particle size of the transition metal salt fine powder is 5 microns.

4. FeCuCoO according to claim 1 x The method for preparing a nano solid solution is characterized in that: In the step S2, during the heating and melting process of NaNO3, the heating rate is 1°C / min to 5°C / min, the temperature is 300°C to 350°C, and the reaction time is 1h to 3h.

5. FeCuCoO according to claim 1 x The method for preparing a nano solid solution is characterized in that: In step S3, the drying temperature is 40° C. to 65° C., and the drying time is 6 h to 12 h.

6. Utilizing the FeCuCoO according to claim 1 x FeCuCoO prepared by the preparation method of nano solid solution x Nano solid solution.

7. FeCuCoO according to claim 6 x Nano solid solution, characterized in that The FeCuCoO x The nano-solid solution is in the form of two-dimensional flakes and has magnetic recovery properties.

8. FeCuCoO as claimed in claim 6 x Application of nano solid solutions in degradation of organic pollutants.